The art and science of analog circuit design - Williams, Jim, 1948-2011. (Boston : Butterworth-Heinemann, 1998)
In this companion text to Analog Circuit Design: Art, Science, and Personalities, seventeen contributors present more tutorial, historical, and editorial viewpoints on subjects related to analog circuit design. By presenting divergent methods and views of people who have achieved some measure of success in their field, the book encourages readers to develop their own approach to design. In addition, the essays and anecdotes give some constructive guidance in areas not usually covered in engineering courses, such as marketing and career development. *Includes visualizing operation of analog circuits *Describes troubleshooting for optimum circuit performance *Demonstrates how to produce a saleable product.
Part One -- Learning How; Part Two -- Making It Work; Part Three -- Selling It; Part Four -- Guidance and Commentary.
Includes bibliographical references and index.
Keywords: Linear integrated circuits -- Design and construction; Electronic circuit design; Electronic books